Reconceptualizing Presumed Consent in Emergency Health Services: Legal Status and Evidentiary Challenges - Endang Sutrisno; Retno Citraning Asih (PT. Islamic Research Publiser, 2026)
Emergency healthcare services often create legal dilemmas because healthcare professionals are obligated to provide immediate life-saving treatment, while high-risk medical procedures generally require prior informed consent. This situation creates legal uncertainty when patients are unconscious or otherwise incapable of providing consent, and no family members or legal representatives are available. Accordingly, this study addresses two research questions: (1) what is the legal status of presumptive consent in emergency healthcare services under Law Number 17 of 2023 on Health, and (2) what is its evidentiary value as a basis for legal protection of healthcare professionals in medical disputes? This study employs a normative legal research method using statutory and conceptual approaches, analyzing primary, secondary, and tertiary legal materials through descriptive-qualitative analysis. The findings reveal that Law Number 17 of 2023 provides an explicit legal basis for applying presumptive consent through Article 80 paragraph (3) and Article 293 paragraph (9) as an exception to the general requirement of informed consent in emergencies. However, its evidentiary value can only be established when medical actions are performed in accordance with professional standards and standard operating procedures, undertaken in good faith for the patient's best interests, and supported by complete and accurate medical records. This study contributes to the academic discourse by developing a legal framework that positions presumptive consent as both a doctrine of legal justification and an evidentiary instrument within Indonesia's health law following the enactment of Law Number 17 of 2023, thereby enriching the literature on legal protection for healthcare professionals in emergency medical services.